Spectrophotometric assessment of vitamins B1, B6 and C with N-bromosuccinimide - Bosch Serrat, F. (Ars Pharmaceutica (Internet), 1970)
Experiences with various vitamins and n-bromosuccinimide allow us to ease the use of this reagent for the assessment of vitamins C, B1 and B6 whenever possible to carry out in a medium with high percentage of methyl alcohol. The collaborations obtained with ascorbic acid, thiamine dichloride and pyridoxine hydrochloride follow Beer’s law fairly accurately between the limits of 0.2-2 mg; 0.2-2 mg and 0.1-1 mg respectively, practicing the reading of the optical density at 370-380mμ. This work includes techniques for the valuation of the mentioned vitamins in medicines, and lists the most important interferences that the method presents.